2004
DOI: 10.3310/hta8450
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and economic evaluation of a long-acting insulin analogue, insulin glargine

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 14 publications
3
50
0
3
Order By: Relevance
“…1), a conclusion that is also supported by a systematic review of glargine (25). It is important to note that, in many cases, longacting insulin analogs, with their improved predictability and flatter absorption profile, can lower the frequency of (nonsevere) nocturnal hypoglycemia (24).…”
Section: Hypoglycemiamentioning
confidence: 87%
See 2 more Smart Citations
“…1), a conclusion that is also supported by a systematic review of glargine (25). It is important to note that, in many cases, longacting insulin analogs, with their improved predictability and flatter absorption profile, can lower the frequency of (nonsevere) nocturnal hypoglycemia (24).…”
Section: Hypoglycemiamentioning
confidence: 87%
“…In contrast, in most studies, severe hypoglycemia has not been reduced by switching to either glargine-or detemirbased MDI regimens (21)(22)(23)(24)(25) (Fig. 1), a conclusion that is also supported by a systematic review of glargine (25).…”
Section: Hypoglycemiamentioning
confidence: 91%
See 1 more Smart Citation
“…(16) Three CUAs found that iGlarg was cost effective compared to iNPH, (45)(46)(47) another found that iGlarg was dominant compared to iNPH,(48) while another found that iGlarg was not cost effective compared to iNPH. (16) One CUA found that iDet was dominant (less costly and more effective) over iGlarg, (44) while another found that iGlarg was the dominant option when compared to iDet.…”
Section: Discussionmentioning
confidence: 99%
“…Esta indicação é reforçada pela heterogeneidade dos resultados na redução da hipoglicemia grave com a utilização do esquema de múlti-plas doses de insulina (MDI), com os análogos de insulina de ação curta e lenta (10)(11)(12)(13)(14)(15). Esses estudos têm mostrado que a utilização desses análogos reduzem as hipoglicemias leves, moderadas e noturnas, mas não as graves.…”
unclassified